Vagal schwannoma in pregnancy: a case report - Patil, Apurva V.; Palve, Tushar T.; Fatemi, Sakina M.; Thatikonda, Rajashree M. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Cervical vagal schwannomas are rare, slow-growing, benign tumours that typically present in patients aged 30–50 years without neurological deficits. Magnetic resonance imaging (MRI) is the gold standard for preoperative diagnosis, while surgical resection remains the treatment of choice. A case report of a 25-year-old pregnant woman with a history of a right-sided neck swelling of 5×4×1 cm since childhood presented for antenatal care which was firm, immobile, and non-tender, with no significant neurological symptoms. Ultrasonography (USG) and computed tomography (CT) scan indicated a neurogenic tumour, most likely schwannoma. MRI in 2024 confirmed a 3.5×4.8×6.3 cm encapsulated, heterogeneously enhancing lesion in the right carotid triangle, consistent with a vagal nerve schwannoma. The tumour caused anterior displacement of the carotid artery and internal jugular vein without significant luminal narrowing. During her pregnancy, the patient remained asymptomatic but developed gestational hypertension postpartum. Neurology and neurosurgery consultations recommended tumour re-evaluation and follow-up after delivery. She underwent an emergency caesarean section at 38 weeks for obstetric indications, with intraoperative monitoring due to vagal nerve stimulation. Postoperative care included antihypertensive management, and the patient was discharged in stable condition with advice to follow up for definitive tumour management. Cervical vagal schwannomas are uncommon and often misdiagnosed due to their asymptomatic nature and resemblance to other neck masses. MRI is crucial for diagnosis, distinguishing vagal schwannomas from other neurogenic tumours based on vessel displacement patterns. Although surgical resection is the definitive treatment, management during pregnancy requires individualized, multidisciplinary care to balance maternal and fetal outcomes. Deferring surgery until postpartum is preferred unless urgent intervention is required. A collaborative approach ensures optimal outcomes for both mother and child.